Bentuk dan Fungsi Pertunjukan Ebeg Turangga Edan di Kelurahan Tegalreja Kecamatan Cilacap Selatan Kabupaten Cilacap - Juniati, Nur Endah (Program Studi Pendidikan Tari FBS UNJ, 2021)
The Ebeg Turangga Edan performance is one of the traditional folk art groups in Cilacap Regency which uses the Ebeg property which is turned into a horse. The research objective was to describe the form and function of the Turangga Edan Ebeg Performance in Tegalreja Village, Cilacap Selatan District, Cilacap Regency. This research uses qualitative methods, with a structure and function approach. Data collection techniques include observation, interviews, and documentation. The data validity technique used triangulation. Data analysis using data reduction, data presentation, and drawing conclusions. The results of the research reveal that the Ebeg show is patterned into several parts, namely the initial part of performing the rituals carried out by the penimbul (Pawang), the core part of the three-act presentation, the final part marked by a mass mendheman scene and the closing remarks from the pengimbul / elder / chairman of the Turangga Edan association. Ebeg show is formed from the relationship between elements of the show which includes themes, actors / dancers, movement, music, make-up and fashion, property / equipment, stage, lighting / light and sound, appreciators / audience. The function of the Ebeg Turangga Edan performance in the community of Cilacap Regency includes the functions of ceremonial facilities, self-expression, entertainment, shows / performing arts, educational media, therapy / treatment vehicles, and communication media / social interaction tools. The conclusion is that the Ebeg Turangga Edan show is patterned into parts that are united into one show. The Turangga Edan Ebeg show is used by the community as entertainment.